Mendorong Model Mental dan Keterampilan Pemecahan Masalah melalui Argumentation-Based on Three Levels of Representation (AB3LR) - Hazrati Ashel; Ida Hamidah; Sjaeful Anwar; Muslim (Jurnal Penelitian Pendidikan IPA, 2025)
Mental models and problem solving skills need to be developed in learning. However, previous study show that students’ mental model and problem-solving skills are not optimal. The solution is to develop an Argumentation Based on Three Levels of Representation (AB3LR) model. This research aims to determine the components, validity, and practicality of the AB3LR model. The method of this study is Design and Development Research (DDR). The instruments used consisted of validation sheets and student response questionnaires. The model was validated by five experts and applied to 19 students taking Statistical Physics courses. The data obtained was analyzed using the Content Validity Ratio (CVR) and Percentage Calculation Method (PCM). The AB3LR model consists of seven stages, namely identifying problems or phenomena, collecting data or information, assimilation and accommodation, presenting tentative arguments, implementing solutions, analyzing and synthesizing the results of discussions, and evaluation. The validation result is 0.99 with a valid category. The AB3LR model is also practical to use with the average percentage is 86.12%. 78.90% and 63.2% students strongly agree that AB3LR model can promote mental models and problem-solving skills. The conclusion of the study is the AB3LR model is valid and practical for use in learning.